Feeding Practices And Nutritional Status Of High Yielding Dairy Animals In S.D.A.U Adopted Villages Of Datiwada Taluka - Gami, Yogesh M.; Bhagawat, S. R.; Raval , Ajay P. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A survey was carried out among the farmers and milk producers of ten villages of Dantiwada taluka of the Banaskantha district which are adopted by Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar for obtaining information on feeding practices and nutritional status of high yielding dairy animals. It was observed that most of dairy animals were stall fed and provided dry and green fodder with various combinations of concentrate mixtures. The TDN and DCP requirements for cattle and buffalo were calculated which was compared for actual availability with the data obtained by proximate analysis.